Public support for bicycling and transport policies in inner Sydney, Australia: a cross‐sectional survey - Chris Rissel; Melanie Crane; Chris Standen; Li Ming Wen; Richard Ellison; Stephen Greaves (Elsevier, 2018)
Abstract Objective: To describe the degree of community support - and factors associated with this support - for a number of potential transport policy options among an inner‐city sample of residents in Sydney, Australia. Methods: This study analysed data collected from a cross‐sectional online survey: Wave 3 of the Sydney Transport and Health Study, conducted in September-October 2015 (n=418). Results: There was a high level of overall support for policies to make public transport cheaper (85%), have more bicycle paths separated from motor vehicles (82%) and have a public bike‐share program (72%), with similar levels of support across usual commute mode, age and sex. Conclusions: Despite a natural tendency for respondents to support transport policies that were of most relevance to themselves, it appeared that, in this sample, public support for public transport and bicycling policies remained strong across all respondents. Implications for public health: Policies that support public transport and active travel and achieve positive health outcomes would be well received by inner‐Sydney residents.